Prebiotic activity of Lactobacillus casei grown on medium containing of Hylocereus undatus extract and its use in the fermentation of goat’s milk kefir - MARIA ERNA KUSTYAWATI; MUKAROMAH EKA NURLITA; ESA GHANIM FADHALLAH; SAMSUL RIZAL (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Kustyawati ME, Nurlita ME, Fadhallah EG, Rizal S. 2022. Prebiotic activity of Lactobacillus casei grown on medium containing of Hylocereus undatus extract and its use in the fermentation of goat’s milk kefir. Biodiversitas 23: 6513-6519. White dragon fruit extract used as a prebiotic source is thought to be an innovative exploration to enhance its application as a synbiotics in food products. This study aims to quantify the prebiotic index and prebiotic activity score for Lactobacillus casei grown on white dragon fruit extract containing media at different concentrations. The study was carried out using a completely randomized design (CRD) experimental method with one factor, concentration of white dragon fruit extract (P1-P5) with 5 levels (2, 4, 6, 8, and 10% respectively), and was repeated 3 times. The data were analyzed statistically by ANOVA, if the treatments were significantly different then the LSD test (5%). The result showed that all tested media had a beneficial effect on the growth of L. casei (prebiotic index higher than 1), while they did not support the growth of enteric Escherichia coli (prebiotic index less than 1 or negative). The highest score of prebiotic activity for L. casei was grown on 10%, while the lowest was 2%. The addition of 10% prebiotic extract of white dragon fruit in goat's milk fermentation produced goat's milk kefir with characteristics that met Codex Stand 243-2003 and had a DPPH radical scavenging activity of 55.13%.